Exploring The Relationship Between Workplace Incivility and Productivity: SME’s Perspective - Imoh Emmanuel, Ph.D., Uwem,; Timilehin Olasoji, Ph.D., Olubiyi,; Arinola Aramide, Ph.D., Kuforiji,; Kabiru, Ishola, Ph.D., Genty, (Lafadz Jaya Publisher, 2022)
Increased productivity in SMEs in terms of quality service delivery is crucial for economic growth and development. Most SMEs are bedevilled with destructive workplace deviant behaviour, particularly the incivility of owners/managers and employees towards customers, which have different consequences for workplace performance parameters such as a decline in sales, low patronage, and by extension, weak gross domestic product contribution. Using the social exchange theory, this cross-sectional study examined the influence of workplace incivility on productivity among 365 owners/managers, supervisors, and employees of SMEs in the liquefied petroleum gas sub-sector in Lagos State. Stratified proportionate sampling was utilized to select the respondents. The outcomes revealed that workplace incivility in the form of rudeness, discourteous disposition, and derogatory remarks predicted productivity in terms of an interaction between customers and employees and the capacity of the service process. Also, our findings accentuated the essence of avoiding direct and indirect costs that are linked with workplace incivility. The study recommended the communal and positive interpersonal relationships between owners/managers, employees, and customers and suggested training on emotional intelligence as a panacea for behavioral responses.